Clinical and imaging findings of neurosyphilis - He, Peng; Ma, Wen-hui; Jiang, Jie; Wang, Wen-sheng; Huang, Cong; Bai, Hong (Frontiers in Neurology, 2025)
BackgroundThis study aimed to systematically analyze the clinical and MRI characteristics of four types of neurosyphilis to improve diagnostic accuracy and facilitate early treatment. By deepening the understanding of clinical presentations and MRI findings, this study seeks to enhance differential diagnosis capabilities.MethodsThis was a retrospective study analyzing clinical and MRI data from 23 patients diagnosed with neurosyphilis between January 2016 and May 2024. MRI examinations were performed using 3-Tesla scanners (Siemens, Germany; General Electric, United States) with an 8-channel head coil. The imaging protocol included T1-weighted imaging (T1WI), T2-weighted imaging (T2WI), fluid-attenuated inversion recovery (FLAIR), diffusion-weighted imaging (DWI), and contrast-enhanced T1-weighted imaging (T1WI-CE) using gadolinium-based contrast agents.ResultsOf the 23 cases of neurosyphilis, including 19 males and 4 females, the mean age was 49.2 ± 11.4 years (range: 27–67). Sixteen cases of parenchymal type (69.6%), mainly manifested as progressive cognitive impairment with psycho-behavioral abnormalities. MRI mainly showed bilateral temporal lobe and hippocampal atrophy with signal abnormalities, with or without abnormal signals in other brain parenchyma, and the enhancement patterns were diverse, which may be unenhanced, patchy, or strip enhancement. Three cases of meningovascular type (13.0%), presented with ischemic stroke with short duration and acute onset. MRI mainly showed multiple acute cerebral infarcts with extensive but scattered intracranial lesions. Three cases of syphilis gumma type (13.0%), had a long course of disease and mainly presented with headache. MRI mainly showed multiple lesions in the internal cerebral convexity with significant surrounding edema bands and significant enhancement of the enhanced lesions with adjacent meningeal enhancement. Mixed type in 1 case (4.4%), presented with headache. MRI findings were complex.ConclusionThe clinical and MRI manifestations of neurosyphilis are diverse, with significant variations among subtypes. Quantitative imaging biomarkers, including lesion volume and SIR, demonstrated diagnostic utility, particularly in distinguishing parenchymal and meningovascular types. Integrating these biomarkers with clinical evaluation may improve diagnostic precision and facilitate targeted interventions.